Socio-Economic determinants of antenatal care utilisation of pregnant mothers in selected health facilities in the Kwabre East district of Ghana. - Akowuah, Jones Asafo (2016)
A Thesis Submitted to the Department of Agricultural Economics, Agribusiness and Extension, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirement for the degree of